Acidentes provocados por Millipede com manifestacoes dermatologicas: Relatos de dois casos - Haddad V., Jr [UNESP]; Costa Cardoso, J. L. [UNESP]; Rotta, O. [UNESP]; Eterovic, A. [UNESP] (My University, 2000)
This study is based on the two case reports of accidents provoked by arthropods (Millepede) in human beings. The authors present this type of accident, the insect specie that caused the accidents, the aggressive mechanism, which is poorly studied in Brazil, and the bibliography.
Accidents provoked by Millipede with dermatological manifestations: Report of two cases
Keywords: Arthropods; benzoquinone; corticosteroid; insect venom; adult; arthropod; blister; case report; erythema; female; human; hyperpigmentation; insect sting; male; skin inflammation; skin manifestation; skin ulcer